The impact of the system of responsibility accounting in the evaluation and control on the quality of the performance of government units at King Abdul Aziz University in Jeddah - Abdulrahman, Najla Ibrahim; Sait, Rana Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to know the impact of the responsibility accounting system on evaluation and control on the performance of government units at King Abdulaziz University in Jeddah, in application at the administrative and academic levels, by surveying the views of officials on the availability of responsibility accounting at King Abdulaziz University and the impact of the use of responsibility accounting. Responsibility in monitoring the improvement of performance effectiveness, and the impact of the use of responsibility accounting in evaluating performance on improving performance effectiveness, and the advantages of applying responsibility accounting in improving performance effectiveness at King Abdulaziz University in Jeddah. To achieve this goal, the descriptive survey method was used for a random sample of officials at King Abdulaziz University in Jeddah, where the questionnaire was distributed to the sample, and the results were analyzed using statistical methods. The effectiveness of its performance, and that the use of the components of responsibility accounting in monitoring and evaluating performance affects the improvement of the effectiveness of performance, and that the advantages of using responsibility accounting affect the improvement of the effectiveness of its performance. Accordingly, the two researchers recommended the necessity of continuing to apply the supervisory methods that help improve the effectiveness of performance, taking into account the establishment of clear and easy standards and thus the possibility of achieving them so that the performance of employees is to the fullest and work on the permanent development of accountability to improve the effectiveness of control and performance evaluation.